Characterization of Methanol Fraction Compounds from Formulation Chinese Senna Leaves (Cassia Alata L.) Using UV-Vis Spectrophotometry Method - Suryadi, A. Mu'thi Andy; Solang, Wicawati Van; Paneo, Mohamad Aprianto (Jurnal Farmasi Teknologi Sediaan dan Kosmetika, 2025)
The leaves of Cassia Alata L. (Chinese Senna) are an important part of daily human life and are used as medicine for treating ringworm, worms, constipation, and canker sores. Cassia Alata L., also known as Gelinggang, has a spicy taste and is warm in nature. This study aims to identify the secondary metabolite compounds present in Formula Cassia Alata L. leaves. The method used in this study is maceration with methanol as the solvent. Qualitative analysis in this study utilized color tests, thin-layer chromatography (TLC) with a hexane:ethyl acetate (4:1) solvent system, and quantitative analysis using UV-Vis spectrophotometry at wavelengths of 260.00 nm, 213.18 nm, 345.24 nm, 202.56 nm, and 363.63 nm. The results show that Cassia Alata L. leaves positively contain flavonoids, alkaloids, steroids, saponins, and tannins. It is concluded that the identification of secondary metabolite compounds from Cassia Alata L. leaves using UV-Vis spectrophotometry with methanol as a solvent provides spectra that correspond to secondary metabolite compounds